FRI0007 High-density lipoproteins suppress the inflammatory response to msu crystals in vivo. (23rd January 2014) - Scanu, A.; Luisetto, R.; Oliviero, F.; Gruaz, L.; Sfriso, P.; Burger, D.; Punzi, L.
Abstract : Background: A characteristic feature of crystal-induced inflammation is that acute attacks are self-limiting even without treatment. Many factors are involved in this spontaneous resolution. Among them, plasma proteins and lipoproteins identified in synovial fluids may modulate crystal-induced inflammation [1, 2 ]. We demonstrated that high-density lipoproteins (HDL) down-regulate chemokine production induced by monosodium urate (MSU) crystals in vitro [3 ]. Objectives: To evaluate the effects and mechanisms of action of HDL in a murine air-pouch model of MSU crystal-induced acute inflammation. Methods: MSU crystals were prepared by Denko's method [4 ] and sterilized by heating at 180°C for 2 h before each experiment. Human HDL were isolated from peripheral blood of healthy volunteers [5 ]. Air pouches were raised on the backs of CD1 mice (n=7 per condition). Various amounts of MSU crystals in 1 ml of PBS were injected into the pouch in the presence or absence of 0.1 mg of HDL for 3h. A group of mice was injected with MSU crystals pretreated with HDL for 1 h, centrifuged and resuspended in PBS. Negative control pouches received 1 ml of PBS. Pouch fluids were recovered by washing with 2 ml of PBS after the animals were sacrificed. Leukocyte count in lavage fluids was obtained using a hemocytometer and the percentage of neutrophils was determined by May-Grünwald-Giemsa staining. IL-1β, IL-6, CXCL1, CCL2 and TNF levels were measured in exudates by ELISA. Simultaneously, air pouch membranes were carefully dissected from adjacent subcutaneous and paraspinal tissues. IL-1β, IL-6, CCL2 and CXCL1 mRNA was isolated from exudate cells and membranes and analyzed by quantitative RT-PCR (qPCR). Results: MSU crystals induced leukocytes infiltration (9.75 ± 1.73 x 10 5 cells/ml) comprising 68.57 ± 6.48 % of neutrophils. IL-1β (34.46 ± 11.03 pg/ml), IL-6 (692.61 ± 235.20 pg/ml), CXCL1 (493.73 ± 32.5 pg/ml) and CCL2 (2035.25 ± 2238.66 pg/ml) were measured in pouch fluids, while TNF levels remained under detection limit. Measurements of cytokine mRNA demonstrate that MSU crystals triggered IL-1β, IL-6 and CXCL1 expression in both pouch exudates and membranes whereas CCL2 mRNA was not modulated. The co-injection of MSU crystals and HDL inhibited leukocyte influx by ≈59% and neutrophil infiltration by ≈83% and, in turn, both protein and mRNA levels of all assessed cytokines were reduced. Similarly, injection of MSU crystals pretreated with HDL diminished leukocyte influx into the pouches and the production and expression of the inflammatory factors tested. Per se, PBS or HDL did not induce cell accumulation and cytokine production in pouches. Conclusions: This study demonstrates that HDL limit the inflammatory response induced by MSU crystals in vivo by inhibiting leukocyte recruitment and cytokine release and expression. HDL inhibit MSU-induced inflammatory cytokine production by both infiltrating cells and pouch tissue cells. By analogy, HDL may represent an important factor modulating gouty inflammation by acting on both synovial tissue and synovial fluid cells. References: Terkeltaub R, et al. J Biol Chem 1986 Terkeltaub RA, et al. J Clin Invest 1991 Scanu A, et al. Arthritis Res Ther 2010 Denko CW, et al. J Rheumatol 1976 Hyka N, et al. Blood 2001 Disclosure of Interest: None Declared